Pengaruh Rekening Dormant dan Dana Pihak Ketiga Terhadap Laba Bank di Bank Syariah Mandiri - K. Khoirunnisa (Faculty of Economic and Business, 2015)
The Effect of Dormant Accounts and Deposit Funds to Bank's Profits in Bank of Sharia MandiriThe purpose of this research is to analyze the effect’s dormant accounts and the amount of third party funds (DPK) to the bank's profit in Bank of Sharia Mandiri. The analysis of the data used in this research is a method of multiple linear regression with the dependent variable is profit and the independent variables are dormant account and third party funds. The result shows that the dormant account didn’t have an effect on bank’s profit. Otherwise, the third party funds/deposit funds has an effect of bank’s profit. This result imply that bank should reduce the dormant account, if there is a decreasing in dormant account there will be an increasing too in third party funds, and if the third party funds is increasing the bank’s profit will be also increasingDOI: 10.15408/etk.v14i1.2264